Does tourism really cause stress? A natural experiment utilizing ArcGIS Survey123. Issue 1 (2nd January 2021) - Jordan, Evan J.; Moran, Casey; Godwyll, Josephine M.
ABSTRACT: Tourism related stress has recently been revealed as an issue for tourism host community residents. Prior studies have relied on directly asking residents if tourism caused them stress, resulting in possible participant priming. This study utilized the ArcGIS Survey123 app to collect data on resident stress from a community with high levels of tourism visitation and a community with low levels of tourism visitation. During the study, researchers never mentioned tourism. Half of study participants in the community with high tourism visitation discussed tourism directly as a stressor, accounting for almost 5% of all stressful experiences, while no participants in the community with low tourism visitation mentioned tourism as a stressor. Geospatial data revealed that tourism related stressors occurred outside of the 'tourism zone' in the community with high tourism visitation, and tourism related stressors mirrored perceived tourism impacts measured in a post experiment survey of study participants.